Distinct Human NK Cell Phenotypes and Functional Responses to Mycobacterium tuberculosis in Adults From TB Endemic and Non-endemic Regions - Harris, Levelle D.; Khayumbi, Jeremiah; Ongalo, Joshua; Sasser, Loren E.; Tonui, Joan; Campbell, Angela; Odhiambo, Felix Hayara; Ouma, Samuel Gurrion; Alter, Galit; Gandhi, Neel R.; Day, Cheryl L. (Frontiers in Cellular and Infection Microbiology, 2020)
Mycobacterium tuberculosis (Mtb) is the causative agent of tuberculosis (TB), which leads to an estimated 1.5 million deaths worldwide each year. Although the immune correlates of protection against Mtb infection and TB disease have not been well defined, natural killer (NK) cells are increasingly recognized as a key component of the innate immune response to Mtb and as a link between innate and adaptive immunity. In this study, we evaluated NK cell phenotypic and functional profiles in QuantiFERON-TB (QFT)+ and QFT- adults in a TB endemic setting in Kisumu, Kenya, and compared their NK cell responses to those of Mtb-naïve healthy adult controls in the U.S. We used flow cytometry to define the phenotypic profile of NK cells and identified distinct CD56dim NK cell phenotypes that differentiated the Kenyan and U.S. groups. Additionally, among Kenyan participants, NK cells from QFT+ individuals with latent Mtb infection (LTBI) were characterized by significant downregulation of the natural cytotoxicity receptor NKp46 and the inhibitory receptor TIGIT, compared with QFT– individuals. Moreover, the distinct CD56dim phenotypic profiles in Kenyan individuals correlated with dampened NK cell responses to tumor cells and diminished activation, degranulation, and cytokine production following stimulation with Mtb antigens, compared with Mtb-naïve U.S. healthy adult controls. Taken together, these data provide evidence that the phenotypic and functional profiles of NK cells are modified in TB endemic settings and will inform future studies aimed at defining NK cell-mediated immune correlates that may be protective against acquisition of Mtb infection and progression to TB disease.